Colonic content in health and its relation to functional gut symptoms. Issue 6 (12th February 2016) - Bendezú, R. A.; Barba, E.; Burri, E.; Cisternas, D.; Accarino, A.; Quiroga, S.; Monclus, E.; Navazo, I.; Malagelada, J.‐R.; Azpiroz, F.
Abstract: Background: Gut content may be determinant in the generation of digestive symptoms, particularly in patients with impaired gut function and hypersensitivity. Since the relation of intraluminal gas to symptoms is only partial, we hypothesized that non‐gaseous component may play a decisive role. Methods: Abdominal computed tomography scans were evaluated in healthy subjects during fasting and after a meal ( n = 15) and in patients with functional gut disorders during basal conditions (when they were feeling well) and during an episode of abdominal distension ( n = 15). Colonic content and distribution were measured by an original analysis program. Key Results: In healthy subjects both gaseous (87 ± 24 mL) and non‐gaseous colonic content (714 ± 34 mL) were uniformly distributed along the colon. In the early postprandial period gas volume increased (by 46 ± 23 mL), but non‐gaseous content did not, although a partial caudad displacement from the descending to the pelvic colon was observed. No differences in colonic content were detected between patients and healthy subjects. Symptoms were associated with discrete increments in gas volume. However, no consistent differences in non‐gaseous content were detected in patients between asymptomatic periods and during episodes of abdominal distension. Conclusions & Inferences: In patients with functional gut disorders, abdominal distension is not related to changes in non‐gaseous colonic content. Hence, other factors, such as intestinal hypersensitivity and poor tolerance of small increases in luminal gas may be involved. Abstract : The distribution of non‐gaseous colonic content was measured using an original program for analysis of abdominal CT images. In healthy subjects intraluminal content was uniformly distributed along the colon and a discrete distal mass movement was observed in the early postprandial period. In patients with functional gut disorders, either during basal conditions or during episodes of abdominal distension, non‐gaseous colonic content was within the normal range.